5-Arylidene-4-Thiazolidinone Derivatives Active as Antidegenerative Agents on Human Chondrocyte Cultures - Panico, Annamaria; Maccari, Rosanna; Cardile, Venera; Crasci, Lucia; Ronsisvalle, Simone; Ottana, Rosaria (Medicinal Chemistry, 2013)
5-Arylidene-2-oxo-4-thiazolidinones and 2-phenylimino analogues were evaluated for their antidegenerative activity on human chondrocyte cultures stimulated by IL-1β and for their inhibitory capability against matrix metalloproteinase- 13. Our results indicated that 5-arylidene-4-thiazolidinone derivatives 1-9 exhibit antidegenerative activity and could block multiple cartilage destruction during the osteoarthritic process. Out of the selected compounds, (5-arylidene- 2,4-dioxothiazolidin-3-yl)acetic acids 7-9 showed significant effectiveness in reducing NO release and restoring normal levels of GAGs in chondrocytes treated with IL-1β. Moreover, benzoic acids 1, 5 and 6 proved to be effective MMP-13 inhibitors and were able to restore normal levels of GAGs.
Keywords: 5-Arylidene- 4-thiazolidinones